2007
DOI: 10.4161/cc.6.3.3752
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Activation in Postmitotic Neurons is Essential for DNA Repair

Abstract: Increasing evidence indicates that maintenance of neuronal homeostasis involves the activation of the cell cycle machinery in postmitotic neurons. Our recent findings suggest that cell cycle activation is essential for DNA damage-induced neuronal apoptosis. However, whether the cell division cycle also participates in DNA repair and survival of postmitotic, terminally differentiated neurons is unknown. Here, we tested the hypothesis that G(1) phase components contribute to the repair of DNA and are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 67 publications
2
72
0
1
Order By: Relevance
“…31 Though several in vivo/in vitro studies showed that CDK inhibitors prevent neuronal apoptosis induced by DNA damage or excitotoxic stress, 31,32 the extent to which cell-cycle proteins are involved in excitotoxicity seems to depend on the insult's strength, oxidative stress, and resulting DNA damage as well as on neurons ability to overcome the acute stress. 31,33 Furthermore, although certain cell-cycle components are essential to DNA repair and neuronal survival, entry into S phase and DNA replication are thought to be lethal for postmitotic neurons. 32,33 Thus, in vivo, Rb stimulation by CXCL12 could counteract the effect of toxic insults that trigger reentry of neurons into cell cycle, such as oxidative stress and DNA damage, which are the underlying cause of neuropathologies associated to excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Though several in vivo/in vitro studies showed that CDK inhibitors prevent neuronal apoptosis induced by DNA damage or excitotoxic stress, 31,32 the extent to which cell-cycle proteins are involved in excitotoxicity seems to depend on the insult's strength, oxidative stress, and resulting DNA damage as well as on neurons ability to overcome the acute stress. 31,33 Furthermore, although certain cell-cycle components are essential to DNA repair and neuronal survival, entry into S phase and DNA replication are thought to be lethal for postmitotic neurons. 32,33 Thus, in vivo, Rb stimulation by CXCL12 could counteract the effect of toxic insults that trigger reentry of neurons into cell cycle, such as oxidative stress and DNA damage, which are the underlying cause of neuropathologies associated to excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…31,33 Furthermore, although certain cell-cycle components are essential to DNA repair and neuronal survival, entry into S phase and DNA replication are thought to be lethal for postmitotic neurons. 32,33 Thus, in vivo, Rb stimulation by CXCL12 could counteract the effect of toxic insults that trigger reentry of neurons into cell cycle, such as oxidative stress and DNA damage, which are the underlying cause of neuropathologies associated to excitotoxicity. 34,35 However, in the present study Rb impairment (and maybe cell cycle reentry) is not essential to NMDA toxicity as the effect of NMDA is not altered by Rb silencing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the DNA-damage response in mitotic cells results in cell-cycle arrest involving the major cell-cycle machinery. In postmitotic cells, DNA damage may result in cell-cycle activation and subsequent arrest, leading to deleterious events in this cell population as well (110,160). However, we have evolved a series of DNArepair pathways to correct the damage, including direct repair (DR), base-excision repair (BER), nucleotide-excision repair (NER), mismatch repair (MMR), homologous recombination (HR), and nonhomologous end joining (NHEJ) (85,86) (Fig.…”
Section: Dna-repair Pathwaysmentioning
confidence: 99%
“…For example, an increase in cyclin D1 levels and its associated kinase activity is observed following DNA damage (an upstream mediator of stroke damage) and ischemic insult (5, 7, 9 -11). In addition, treatment with pharmacologic cyclin-dependent kinase (Cdk) 3 inhibitors such as flavopiridol protects neurons from both DNA damage-and ischemia-induced cell death (4,6,7). Expression of a dominant negative form of Cdk4, an important regulator of the G 1 /S phase of the cell cycle, is protective following DNA damage and global cerebral ischemia (5,9).…”
mentioning
confidence: 99%